Flame Retardancy, Thermal and Mechanical Properties of Novel Intumescent Flame Retardant/MXene/Poly(Vinyl Alcohol) Nanocomposites - Xiaofei Yan; Jie Fang; Jianjun Gu; Chenkai Zhu; Dongming Qi (Nanomaterials, 2022)
Poly(vinylphosphonic acid) (PVPA) and polyethylenepolyamine (PEPA) are used as novel intumescent flame retardants to improve the properties of MXene (2D Ti3C2Tx)/poly(vinyl alcohol) (PVA) nanocomposites. We investigated the flame-retardant properties, thermal stability, and mechanical properties of MXene/PVA nanocomposites. The results show that MXene was homogeneously dispersed in the PVA matrix containing PVPA and PEPA. PVPA and PEPA effectively improved the flame-retardant properties of MXene/PVA nanocomposites and they did not obviously change the thermal degradation of the MXene/PVA nanocomposites. Moreover, MXene improved the thermal stability of the PVA matrix. The elongation at break of MXene/PVA nanocomposites reached its maximum when the MXene mass fraction was 1.0 wt.%, regardless of whether PVPA and PEPA were present in the PVA matrix, whereas the tensile strength and Young’s modulus of MXene/PVA nanocomposites increased with the increase in MXene content in the PVA matrix.